2021
DOI: 10.25082/amler.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and issues of STEM education

Abstract: Science, Technology, Engineering, Mathematics, abbreviated as STEM, is a promising field with increasing popularity due to its benefits in the modern world of globalization and modernization. Science and mathematics are the basics of the technological developments going on in the world. Thus, the children should be motivated to learn STEM from early school days. The minds of small kids are like a sponge, and they can grasp everything quickly. STEM education should be encouraged from childhood so that children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Source: https://www.oecd.org/pisa/publications/PISA2018 CN GRC.pdf An important recent initiative to provide robotic equipment, for all students, in mandatory education aims to create the conditions for effective integration of S.T.E.M. activities into the curriculum (Qureshi & Qureshi, 2021). The successful implementation of the project will imply a substantial acceptance of the S.T.E.M.…”
Section: Stem Education In Greecementioning
confidence: 99%
“…Source: https://www.oecd.org/pisa/publications/PISA2018 CN GRC.pdf An important recent initiative to provide robotic equipment, for all students, in mandatory education aims to create the conditions for effective integration of S.T.E.M. activities into the curriculum (Qureshi & Qureshi, 2021). The successful implementation of the project will imply a substantial acceptance of the S.T.E.M.…”
Section: Stem Education In Greecementioning
confidence: 99%
“…On the other hand, the authors [7], developed a mobile application focused on augmented reality in order to benefit the learning of sign language, through the Mobile-D methodology. For this, they used a sample of 30 people to perform a control, based on performance results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For this, they used a sample of 30 people to perform a control, based on performance results. The authors [7], in their research work, concluded that their mobile application managed to reduce the learning time of sign language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Globally, digital learning platforms and tools play a significant role in higher education Mohammed, 2022;Papadakis, 2022). Like in developing countries (Qureshi & Qureshi, 2021) like Nepal, where online course delivery is commonplace, course facilitators have used various collaborative tools for course delivery and evaluation (Kalogiannakis & Papadakis, 2007;. These resources include Moodle's discussion forum, workshops, chat rooms, comment sections, wikis, Google Apps docs, slides, and Jamboard (Bower & Wittmann, 2009;Dahal & Pangeni, 2019;Dahal et al, 2020;Dahal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%